Cost of Debt and Corporate Information Transparency Under Economic Depression: The Case of Greek Family-Controlled Firms - Aikaterini Bethani; Constantinos G. Chalevas; Christos A. Tzovas (Journal of Accounting and Management Information Systems (JAMIS), 2019)
Research Question: This study investigates whether corporate information opacity affects the association between family ownership and cost of capital. Motivation: Firms' ownership structure has been identified as a major factor that affects their cost of capital. Idea: Corporate transparency affects the impact of ownership structure upon firms' cost of capital, especially in the case of family-controlled firms Data: We examine a sample of companies listed in the Athens Stock Market for the period of 2009-2016. Tools: We compose a Corporate Opacity Index for each sample firm by adopting the Anderson et al. (2009) approach. Additionally, accounting factors such as firms' size, leverage, profitability and corporate governance characteristics that may affect the above-mentioned association are examined as well. Sensitivity tests have been conducted to check the robustness of the results. Findings: Family ownership and corporate opacity are only marginally related with firms' cost of capital. Firms' size, liquidity and their leverage appear to be inversely associated with their cost of debt capital. Contributions: The findings of this study provide insights regarding the impact that corporate transparency has upon cost of debt capital, allowing financial institutions, regulators and market participants to design improved debt contracts under economic depression. Our study sheds light to the impact of information opacity on the association between family ownership and cost of capital within the business environment of Greece that possesses certain structural characteristics in the context of economic crisis.
Keywords: G1; G3; M4; O16; 650; corporate transparency; family-ownership; economic crisis